ANALISIS KOMPREHENSIF SIFAT FISIK DAN SIFAT KIMIA TANAH SEBAGAI INDIKATOR KESUBURAN TANAH PADA LAHAN PERTANIAN DI KOTA LANGKAT - Harahap, M. Farhan; Sinaga, Ferdi; Adelia, Celine Loise; Fransisko, Beriasi; Prayoga, Oktavian (Institute of Computer Science (IOCS), 2025)
This study was conducted to evaluate the physical and chemical characteristics of the soil as the main determining factor for agricultural land fertility in the Langkat City area. Soil samples were taken in composite from five observation points and analyzed in the laboratory. The parameters analyzed included bulk density, total porosity, particle density, soil water content, pH, and organic carbon and organic matter content. The measurement results showed a bulk density value of 1.18 gr/ml, porosity of 46%, and particle density of 2.34 gr/ml. The dry air water content was recorded at 11.2%, while the field capacity water content was 38%. The soil pH value was in the range of 5.3 to 6.2. The content of C-organic and organic matter was 1.83% and 3.15%, respectively. Based on these results, the soil is classified as having a moderate level of fertility and is still suitable for agricultural activities with appropriate management strategies.